2017
DOI: 10.1063/1.5001206
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear structures and anomalous transport in partially magnetized E×B plasmas

Abstract: Nonlinear dynamics of the electron-cyclotron instability driven by the electron E × B current in crossed electric and magnetic field is studied. In nonlinear regime the instability proceeds by developing a large amplitude coherent wave driven by the energy input from the fundamental cyclotron resonance. Further evolution shows the formation of the long wavelength envelope akin to the modulational instability. Simultaneously, the ion density shows the development of high-k content responsible for wave focusing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 50 publications
7
49
0
Order By: Relevance
“…They too observe modulations in the sheath, however. In our simulations, the anomalous electron transport sets at the level similar to that in our 1D simulations 21 , perhaps due to the absence of secondary emission.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…They too observe modulations in the sheath, however. In our simulations, the anomalous electron transport sets at the level similar to that in our 1D simulations 21 , perhaps due to the absence of secondary emission.…”
Section: Discussionsupporting
confidence: 77%
“…Our simulations demonstrate that like in the 1D case, the instability is driven by nonlinear cy-clotron resonance modes that dominate the anomalous transport, and that the cascade to long wavelengths observed in 1D simulations is further enhanced by the linear long wavelength instabilities that occur when finite k z is allowed. Moderate values of the anomalous electron current (of the order of Ω = Ω ce /ν ef f 200 are obtained in nonlinear stage similar to the 1D case 21 . An important new result is strong parallel electron heating due to the modes with a finite k z .…”
Section: Introductionsupporting
confidence: 55%
“…Although the presence of the E Â B EDI is ubiquitous in PIC simulations including the azimuthal direction under the conditions of Hall thrusters, there is no consensus on its evolution toward a modified ion acoustic instability. Using a highly resolved 1D azimuthal PIC simulation under conditions of Hall thrusters, Janhunen 21 et al showed that the level of turbulence required for the transition to the ion acoustic instability is not reached. They observe a large coherent mode driven mainly at the electron cyclotron drift resonance, and energy flow to long wavelength and low frequency modes.…”
Section: Discussionmentioning
confidence: 99%
“…7,16,18, and 19 seem to be consistent with the scaling of the ion acoustic instability and saturation by ion wave trapping. However, in the recent 1D PC simulations of Janhunen et al, 21 the authors claim that transition to the ion acoustic instability does not occur because the demagnetization condition due to nonlinear resonance broadening is not fulfilled for the electrons.…”
Section: Two-dimensionalmentioning
confidence: 99%
“…These instabilities are very dependent on the specific conditions or regions of a particular device. For example, in a Hall thruster, the large electric field that is present in the acceleration region (quasineutral, collisionless plasma) is responsible for the development of the Electron Cyclotron Drift Instability (ECDI) or E B Electron Drift Instability which has been the subject of many recent studies 7,8,18,19,[40][41][42][43] . This instability leads to anomalous transport but the effective Hall parameter associated with it is relatively large (larger than 100 according to the PIC-MCC simulations 43 ).…”
Section: Introductionmentioning
confidence: 99%